2009
DOI: 10.1007/s12551-009-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels involved in cold detection in mammals: TRP and non-TRP mechanisms

Abstract: Substantial progress in understanding thermal transduction in peripheral sensory nerve endings was achieved with the recent cloning of six thermally gated ion channels from the TRP (transient receptor potential) super-family. Two of these channels, TRP melastatin 8 (TRPM8) and TRP ankyrin 1 (TRPA1), are expressed in dorsal root ganglion (DRG) and trigeminal ganglion (TG) neurons, are activated by various degrees of cooling, and are candidates for mediating gentle cooling and noxious cold, respectively. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 76 publications
(96 reference statements)
1
6
2
Order By: Relevance
“…Cooling the skin to 4°C activates A- and C-fibers sensitive to innocuous cooling and cold-sensitive nociceptors (27-29, 67, 69), consistent with the presence of two populations of cold-sensitive neurons observed in culture (70)(71)(72). Cool-sensitive nonnociceptive afferents are spontaneously active at normal skin temperature and their excitability increases with decreasing temperature (53,67).…”
Section: Transduction Of Noxious Coldsupporting
confidence: 56%
“…Cooling the skin to 4°C activates A- and C-fibers sensitive to innocuous cooling and cold-sensitive nociceptors (27-29, 67, 69), consistent with the presence of two populations of cold-sensitive neurons observed in culture (70)(71)(72). Cool-sensitive nonnociceptive afferents are spontaneously active at normal skin temperature and their excitability increases with decreasing temperature (53,67).…”
Section: Transduction Of Noxious Coldsupporting
confidence: 56%
“…Indeed, we observed a significant decrease in the fraction of R 9 -TAMRA-positive cells in the presence of the non-selective cation channel inhibitors La 3+ and ruthenium red ( Figure 7 A). Since members of the TRP family of non-selective cation channels, namely TRPA1 and TRPM8, have been implicated in cold sensing in vivo and demonstrate a cold-activated current response in vitro [ 29 , 30 ], we assessed their involvement in cold-induced R 9 -TAMRA entry. Neither specific antagonists of TRPA1 HC030031 and AP18 nor specific antagonists of TRPM8 channel AMTB inhibited cold-induced entry of R 9 -TAMRA ( Figure 7 B).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, many afferent cold‐sensitive neurons do not express either the TRPM8 or the TRPA1 protein, and it is suggested that several other channels, in particular potassium channels, may be involved in the responses of afferent neurons to cold stimuli (Munns et al. , 2007; Babes, 2009).…”
Section: Discussionmentioning
confidence: 99%